Trading competition: Upaya peningkatan portofolio keuangan mahasiswa - Aimi, Fanny Nurul; Arismaya, Anisa Dewi (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
Community service through investment education classes and trading competitions in the Islamic capital market class of the Islamic Business Management Study Program, FEBI UIN Salatiga, aims to enhance financial literacy and students' understanding of portfolio management. Good financial literacy is a fundamental necessity for students to make wise financial decisions and avoid risky investments. This activity is designed to provide insights into investment concepts, risk management strategies, and hands-on trading practices through competitive simulations. The methods used in this program include interactive education sessions conducted by the Indonesia Stock Exchange and Mirae Asset Securities, market analysis training, and a trading competition aimed at developing students' investment decision-making skills. The results of this program indicate an improvement in students' knowledge and understanding of investment principles, portfolio diversification strategies, and the importance of risk management in financial markets. Through this initiative, students are expected to become more aware of the importance of early investment and be able to manage their finances more effectively in the future. Moreover, this program contributes to fostering a sustainable and healthy investment ecosystem among the younger generation.